Analytic hierarchy process-based analysis to determine the barriers to implementing a material efficiency strategy: electrical and electronics’ companies in the Malaysian context - Haw, Ho Fu; Abdul-Rashid, Salwa Hanim; Raja Ghazilla, Raja Ariffin (MDPI Open Access Journals, 2018)
Material efficiency is one of the most important strategies for helping manufacturing companies achieve sustainability in their production activities. However, there are many barriers to the implementation of material efficiency strategies in the manufacturing processes and overall business operations. The aim of this study is to identify and evaluate the barriers faced by Electrical and Electronics (E&E) manufacturing companies in Malaysia in implementing material efficiency strategies. A mixed-mode research method was employed to collect data from these companies. Semi-structured interviews were used to identify the barriers faced by the Malaysian Electrical and Electronics (E&E) industry, while an Analytic Hierarchy Process (AHP) survey was utilized to determine the importance of each barrier. Seven companies participated in the semi-structured interviews, and 18 companies took part in the AHP survey. Nine barriers were generated from analysis of the interviews, and were then ranked by priority using the AHP method. These important findings could be used as a guide for E&E companies in managing or overcoming barriers during the implementation of material efficiency strategies and other sustainable manufacturing activities